Effectiveness of nonpharmacological therapeutic interventions on pain and physical function in adults with rib fractures during acute care: A systematic review and meta-analysis - Beverley J. Weinberg; Ronel Roos; Heleen van Aswegen (AOSIS, 2022)
Background: Rib fractures are a common thoracic injury and notable source of chest pain. Chest pain may lead to compromised respiratory and physical function. Objectives: Our study aimed to synthesise the evidence on the effectiveness of nonpharmacological therapeutic interventions on pain and physical function in adults admitted with rib fractures to acute care settings. Secondary outcomes included length of stay (LOS), respiratory complications, respiratory function and mortality rate. Method: A systematic literature search of English articles in nine databases was conducted. The Joanna Briggs Institute's System for the Unified Management, Assessment and Review of Information (SUMARI) was used to conduct our study. Articles written from January 2000 to December 2017 were considered and a search update was completed in 2021. Meta-analysis was conducted for pre- versus post-bundle of care implementation for LOS, pneumonia incidence and mortality rate. Certainty of evidence was appraised using the grading of recommendations, assessment, development and evaluation (GRADE) approach. Results: Sixteen studies were included (n = 2034). Certain interventions were shown to improve respiratory function and reduce pain, pulmonary complications, LOS and mortality rate. No interventions were identified which objectively improved physical function. Meta-analysis showed a statistically significant reduction in relative risk of developing pneumonia (p = 0.00) by 63% following bundled care implementation. Certainty of evidence for this outcome was rated as very low following GRADE appraisal. Conclusion: Nonpharmacological therapeutic interventions used in combination with pharmacological management are viable treatment options to reduce pain, improve respiratory function and reduce the incidence of respiratory complications following acute rib fractures. Clinical implications: Acupuncture, transcutaneous electrical nerve stimulation (TENS), noninvasive ventilation (NIV) modalities, physiotherapy techniques and multidisciplinary pathways used alongside pharmacological interventions are effective modalities for use in the treatment of acute rib fractures. Multidisciplinary care pathways are important management strategies and reduce the risk of developing pneumonia.